Penentuan Harga Normatif pada Kegiatan Operasional Pihak Ketiga Cleaning Service di Uptd Blud RSUD Kabupaten X - Sasanti, Elin Erlina; Putra, I Nyoman Nugraha Ardana; Muhsyaf, Saipul Arni; Animah, Animah (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2022)
UPTD BLUD RSUD Regency X is one of the UPTDs that has been in the form of a Regional Public Service Agency (BLUD) where some of its operational activities use the services of third parties. One of the operational activities that use third parties is cleaning service (CS) whereas, with the end of the hospital's work contract with the previous third party, there is a need for comprehensive analysis and calculation to assess the feasibility of the price of providing services offered by third parties, especially before the contract took place and signing of a new employment contract completed. This research is carried out using applied research. Using economic analysis, this research focuses on providing recommendations on normative prices that are feasible to be applied in the procurement of cleaning services. Based on data analysis from the results of experiments and field observations, three alternative cost results were obtained as a basis for determining the amount of contract value to third parties related to cleaning services. The difference between these three alternative costs lies in the amount of labor required so that it has an impact on the number of costs that will be incurred per month. This study recommends optimizing the number of workers and providing Standard Operating Procedures (SOPs) for the suitability of specifications and the use of tools and materials in order to achieve operational cost efficiency for UPTD BLUD RSUD Regency X.